Dissolution behavior of CaO-MgO-SiO2-based bioceramic powders in simulated physiological environments. Issue 13 (September 2017) - Huang, Mengyuan; Zhang, Mengjiao; Yao, Dajing; Chen, Xianchun; Pu, Ximing; Liao, Xiaoming; Huang, Zhongbing; Yin, Guangfu
Abstract: In this study, the dissolution behavior of CaO-MgO-SiO2 -based bioceramics was investigated in vitro by using a stage-by-stage simulating physiological environment method. Preliminary dissolution rules of CaO-MgO-SiO2 -based bioceramics are presented by soaking akermanite, bredigite, and diopside powders in saline solution. Dissolved Ca and Mg ion concentrations were proportional to the chemical composition of the bioceramics, while the dissolution of Si ion was more affected by their crystal structure. The analysis of zeta potential indicated that ions (possibly including both the dissolved and intrinsic ions) would be adsorbed on the surface of bioceramic powders during soaking in saline solution. Further studies of the dissolution of akermanite powder was performed using different solid-liquid ratios in simulated body fluid (SBF) and α-MEM culture medium. It was found that hydroxyapatite was formed on the surface of akermanite in SBF and amino-containing compounds attracted to the surface of the powders in α-MEM culture medium would impede the diffusion of ions to delay ions release and weaken hydroxyapatite formation. When akermanite powders were co-cultured with BMSCs, HUVECs, or L929 cells, the concentrations of Ca, Mg and Si ions in the solution were lower than that in cell-free medium. Additionally, the pH value gradually decreased with soaking time, unlike what occurs when the materials are soaked in cell-free media, suggesting effects due to the cellular intake of related ions and the release of acidic cellular metabolites. The akermanite extracts in a certain concentration range could promote cell proliferation via cellular intake of related ions. In turn, this ion consumption would affect the dissolution behavior of bioceramics in simulated physiological environments. Graphical abstract: